Manajemen Pengaduan Masyarakat di Pusat Pengelolaan Pengaduan Masyarakat (P3M) Kota Semarang - Cuher Santoso; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Semarang city is one of the cities receiving the most complaints compared to other regencies / cities in Central Java. Public complaints are seen as very important because the current public service paradigm has reached a responsive service, creating a great space for the community to participate in any public policy making, more democratic and provide services in line with the public interest. The Community Complaint Management Center (P3M) as the complaint management unit is established through the Mayor of Semarang's Regulation No. 31 of 2014 on the Semarang City Complaints Management Center. The Community Complaint Management Center (P3M) is expected to provide good public services and manage complaints management effectively and efficiently so as to make Semarang City better.Complaints data from January to June recorded 2978 complaints, 225 requests for information and 295 aspirations. This study aims to describe the Complaints Management Society at the Center for Complaints Management Society (P3M) Semarang City. The research method used is descriptive qualitative using management theories. Results of field research indicate that in the implementation of public services in managing complaints at the Center for Community Complaint Management (P3M) there are still many unmanaged complaints, such as timeliness.Based on the problems found in the study, the authors provide recommendations to improve existing problems include: Improving the quality of public services in managing complaints, socialization to the community about the work unit of Community Complaint Management Center (P3M) is not known to the public, in the field and make a complaint application system that can be used by all elements of the community and can monitor the complaint process.